Narrations of the Left Behind by Al-Bayhaqi - A Critical and Applied Study in the Book Shuab Al-Iman - (Islamic Sciences Journal, 2023)
The term abandoned in the imams of the hadith is given to those who had a lot of illusions and negligence and to the hadeeth whose narrator was a ccused of telling lies. AL-Bayhaqi gave it to nine narrators in his book The People of Faith. The study of the nine narrators hadeeths show that seven of their hadeeths owned only by those narrators who were accused of telling lies, four hadeeths had weak evidences, three of them had no evidence, and only one hadeeth was true, suspended, and brief.
Keywords: Al-Bayhaqi, Al-Matruk, Abu Hurairah, may God be pleased with him, told us. Muhammad bin Hamid told us. Abdullah bin Masoud told us. Anas bin Malik told us .